2017
DOI: 10.1155/2017/7108458
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Source and Cell Expansion Condition Influence Phenotypic Changes of Adipose-Derived Stem Cells

Abstract: Stem cells derived from the subcutaneous adipose tissue of debrided burned skin represent an appealing source of adipose-derived stem cells (ASCs) for regenerative medicine. Traditional tissue culture uses fetal bovine serum (FBS), which complicates utilization of ASCs in human medicine. Human platelet lysate (hPL) is one potential xeno-free, alternative supplement for use in ASC culture. In this study, adipogenic and osteogenic differentiation in media supplemented with 10% FBS or 10% hPL was compared in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…The procoagulant effects of CCTs in trauma patients must be considered as a safety release criterion for their clinical use. Consideration should be given to choosing cell sources expressing less TF and cell expansion methods that minimize TF expression should also be explored …”
Section: Discussionmentioning
confidence: 99%
“…The procoagulant effects of CCTs in trauma patients must be considered as a safety release criterion for their clinical use. Consideration should be given to choosing cell sources expressing less TF and cell expansion methods that minimize TF expression should also be explored …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the concentration of growth factors seems to be limited in both hS and FBS, and some authors found that the debris, that forms during PRP production, could slow down cell expansion [ 6 , 14 ]. However, the relative advantages of these different culture media additives are still widely debated and recent studies showed that particularly hPL could be a valid substitute for FBS, retaining stem cell phenotype (positive expression of CD (cluster of differentiation) CD73, CD90, CD105, but negative for CD34 and CD45) and multilineage differentiation capacity (osteogenic, adipogenic and chondrogenic) of hMSCs [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that Stemulate™ is used to expand a range of cell types, including adipose-derived mesenchymal stem cells (MSCs) and bone-marrow MSCs, it could be an alternative supplement to increase chondrocyte proliferation for cartilage cell therapy (Badowski et al, 2017;Juhl et al, 2016;Mangum et al, 2017;Riis et al, 2016;Søndergaard et al, 2017). Stemulate™ could reduce time in monolayer culture and reduce exposure to tissue-culture plastic, which in turn could reduce the risk of de-differentiation.…”
Section: Introductionmentioning
confidence: 99%